Family planning in a rural-urban fringe area of Thailand : a case study in Pathumthani province - Choi, Chung Bok; Weber, Karl E.; Dias, Hiran D.; Goede, J.H. de; Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1979)
This i s an exploratory study about the family planning program at the provincial level of Changwat Pathumthani, Thailand. The objectives are to examine the service delivery of the family planning program in conjunction with the women-centered s ingle approach of the present policy, and to find the cause of the worst performance rate of the program in this particular province. Data analysis was based on two interview schedules with 280 husbands drawn from four major occupational groups in four Amphoes, and 33 health personnels working in the same four Amphoes. Service records and relevant Also the farmer group was found t o be the target group most in need of education in birth control methods. current users was limiting of births. The primary concern of the This indicates that target people need a permanent method. Yet, the interview samples has a poor knowledge of the methods, and health units in the province are not ready to cope with the problem. government documents supplemented this data. The results of the survey were mainly analyzed by simple descriptive statistics in the form of tables. The study result shows that the women-centered approach of the present policy causes serious problems in the implementation of the program in the province. However, the overall service delivery of the family planning program in the province was not so bad as the government statistics indicated. This finding was reached upon examining the rate of current practice, the pattern of providers, the inaccurate evaluation method, the high level of satisfaction toward providers, and the health personnel's opinion.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1979
Keywords: Birth control -- Thailand -- Pathum Thani